Computer Simulations of Welch Based Denoising Technique for a Set of Chirp Signals Corrupted by Gaussian Noises - Fendy Santoso (Journal of ICT Research and Applications, 2008)
The aim of this research is to investigate the performance of Welch based de-noising technique for a set of chirp signals corrupted by Gaussian noises. In telecommunications, chirp signals are widely studied, particularly for sonar, radar and spread spectrum applications. However, unlike conventional signals, chirp signals are typical of time varying frequency signals. It sweeps linearly from a low to a high frequency. It is in fact a signal in which its frequency increases or decreases with time. Results indicate that Welch based de-noising technique has effectively inhibited the noise. Nevertheless, this method works satisfactory only below its threshold point. Beyond this limit, the signal-to-noise ratio of the desired signal is not acceptable. Figuratively, radar can only detect the presence of the aircraft only at a certain limited distance only. As soon as the aircraft moves further apart, the transmitted signal becomes substantially weaker before the noise can completely overwhelm it. It turns out that the presence of the aircraft is no longer perceptible.